Highlights from the tenth ISCB Student Council Symposium 2014. Issue 2 (December 2015) - Rahman, Farzana; Wilkins, Katie; Jacobsen, Annika; Junge, Alexander; Vicedo, Esmeralda; DeBlasio, Dan; Jigisha, Anupama; Di Domenico, Tomás
Abstract This report summarizes the scientific content and activities of the annual symposium organized by the Student Council of the International Society for Computational Biology (ISCB), held in conjunction with the Intelligent Systems for Molecular Biology (ISMB) conference in Boston, USA, on July 11th, 2014.